Development of a novel rodent model for dog heartworm microfilaremia using the severe-combined immunodeficiency mouse - Mihoko Mizuseki; Nao Ikeda; Takahiro Shirozu; Maki Yamagishi; Sugao Oshiro; Shinya Fukumoto (Scientific Reports, 2024)
Abstract Dirofilaria immitis is a mosquito-borne parasitic nematode that causes fatal heartworm disease in canids. The microfilariae are essential for research, including drug screening and mosquito-parasite interactions. However, no reliable methods for maintaining microfilaria long-term are currently available. Therefore, we used severe combined immunodeficiency (SCID) mice to develop a reliable method for maintaining D. immitis microfilaria. SCID mice were injected intravenously with microfilariae isolated from a D. immitis-infected dog. Microfilariae were detected in blood collected from the tail vein 218 days post-inoculation (dpi) and via cardiac puncture 296 dpi. Microfilariae maintained in and extracted from SCID mice showed infectivity and matured into third-stage larvae (L3s) in the vector mosquito Aedes aegypti. L3s can develop into the fourth stage larvae in vitro. Microfilariae from SCID mice respond normally to ivermectin in vitro. The microfilariae in SCID mice displayed periodicity in the peripheral circulation. The SCID mouse model aided in the separation of microfilariae from cryopreserved specimens. The use of SCID mice enabled the isolation and sustained cultivation of microfilariae from clinical samples. These findings highlight the usefulness of the SCID mouse model for studying D. immitis microfilaremia in canine heartworm research.